GUIDELINES FOR EXCIMER LASER REFRACTIVE SURGERY ON CORNEA - Gil, Joao Quadrado (2015)
Refractive surgery has undergone an extraordinary growth in recent decades, both in technical sophistication and in its popularity among patients. The goal of this work is to present current concepts on corneal Excimer laser refractive surgery. The authors, based on a comprehensive review of the literature and on their own experience, discuss practical topics regarding patient selection and evaluation, procedure choice, different aspects of surgical technique, and post-operative follow-up recommendations. The discussion is focused on the two most popular Excimer procedures: LASIK and PRK. Clinical good conduct regarding patient evaluation is reviewed, focusing on appropriate patient selection and on rigorous assessment of the patient’s pre-operative status. Contra-indications, absolute and relative, as well as specific advantages of both procedures are discussed. Optimal maximum attempted correction values are proposed. The importance of rigorous screening for post-operative ectasia at-risk patients is acknowledged. New advances in screening devices and concepts are discussed. Long-term follow-up of patients is essential for outcome analysis and improvement: practical guidance is suggested and long-term results available are reviewed.